Analisis Framing Pemberitaan Konflik Hamas-Israel pada Media Online Kompas.com dan The New York Times - Marshelli; Suyanto (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
The Gaza-Israel conflict, ongoing since 1948, reignited on October 7, 2023, with a series of rockets fired by Hamas into Israel. This study analyzes the framing of the Hamas-Israel conflict in online media, specifically Kompas.com and The New York Times, using Robert N. Entman's framing analysis, which includes defining problems, diagnosing causes, making moral judgments, and offering treatment recommendations. This qualitative research examines 20 news articles to explore how each outlet shapes perceptions of reality. Results reveal that Kompas.com emphasizes specific facts and figures, while The New York Times highlights emotional impacts. In diagnosing causes, Kompas.com connects the issue to the suffering of Palestinians, whereas The New York Times focuses on the broader Israel-Hamas conflict. For moral judgment, Kompas.com draws on historical context and direct impacts, while The New York Times condemns violence and stresses empathy for human suffering. Regarding treatment recommendations, Kompas.com rarely presents explicit solutions, while The New York Times advocates for international diplomacy and broader approaches.